Doing good instead of doing well? What lawyers could be doing in a world of “too many” lawyers - Menkel-Meadow, Carrie Joan (Oñati Socio-Legal Series, 2013)
This paper explores some of the misalignment in the legal profession in terms of allocation to particular parts of the profession. The paper suggests that there are not “too many lawyers,” but that lawyers could and should be doing other things, beyond conventional forms of legal representation, both for access to justice, and for transformations of the legal system and human problem solving. Lawyers can perform different roles in dispute resolution (mediating, arbitrating, negotiating, as well as litigating), including performing design functions for organizations and other sites of iterated disputes, advising individuals and entities about how to handle and “manage” conflict in order to actually reduce the need for conventional legal services. The paper explores issues of what constitutes “legal knowledge and expertise” and how such knowledge might be deployed to solve complex social and legal problems outside of conventional legal professional boundaries. Contrasts are made with other areas of expertise and the restructuring of professional knowledge in other fields such as business consulting and architecture. The paper concludes by suggesting that lawyers and legal educators need to proactively reframe what is considered to be legal work and legal education for new ways of legal and human problem solving to be studied and learned.